Empati dan penggunaan situs jejaring sosial sebagai faktor dalam membentuk moral remaja - Selviana, Selviana (Konsorsium Psikologi Ilmiah Nusantara, 2016)
This study aimed to look at the effect of empathy and the use of social networking sites as factors to moral behavior of adolescents. The subjects of this study were 294 students of grade 10th and 11th years of a public high school at Bekasi. Results showed that empathy directly affects moral behavior, which means that when the level of empathy is improved, it can form morals into a better direction. Meanwhile, the use of social networking sites affects moral behavior directly, which means that when the use of social networking sites are used for positive things, it can shape moral and when used for negative purposes, it will be the opposite. The findings demonstrate empathy and the use of social networking sites in shaping moral.